Effects of fun-seeking and external locus of control on smoking behaviour: a cross-sectional analysis on a cohort of working men in Singapore - Lee, Alvin Kar Fye (2023)
Objectives: We examined the combined effects of behavioural inhibition and behavioural activation, on one hand, and locus of control, on the other hand, on different categories of smoking behaviour (non-smoking, ex-smoking, occasional smoking, daily smoking). Design: This study adopted a cross-sectional design. Participants completed questionnaires regarding demographics, smoking patterns, behavioural inhibition/behavioural activation systems and locus of control. Setting: The study was conducted across four companies from the transportation, cooling plant and education sectors in Singapore. Participants: Three hundred sixty-nine male working adults were included in the final sample. Results: Corroborating previous research, a logistic regression model examining behavioural inhibition/behavioural activation systems revealed that the fun-seeking aspect of behavioural activation was a unique predictor in distinguishing non-smokers from daily smokers (OR=1.24, p=0.012). By contrast, in a separate model examining locus of control, external locus of control was found to be a unique predictor in distinguishing non-smokers from daily smokers (OR=1.13, p<0.001). In addition, a third model combining both behavioural inhibition/behavioural activation systems and locus of control found that only external locus of control remained a significant predictor (OR=1.12, p<0.001). Further analyses revealed a mediating effect of external locus of control on the relationship between fun-seeking and smoking behaviour. That is, the increase in the odds of daily smoking due to fun-seeking was explained by external locus of control (direct pathway OR=1.20, p=0.058; indirect pathway OR=1.04, p<0.050). Conclusions: Overall, fun-seeking through its influence on external locus of control indirectly affects daily smoking behaviour, suggesting a more complex relationship than shown in previous research.